Galileo's middle finger : heretics, activists, and the search for justice in science - Dreger, Alice Domurat (Penguin Press, 2015)
"An investigation of some of the most contentious debates of our time, Galileo's Middle Finger describes Alice Dreger's experiences on the front lines of scientific controversy, where for two decades she has worked as an advocate for victims of unethical research while also defending the right of scientists to pursue challenging research into human identities. Dreger's own attempts to reconcile academic freedom with the pursuit of justice grew out of her research into the treatment of people born intersex (formerly called hermaphrodites). The shocking history of surgical mutilation and ethical abuses conducted in the name of "normalizing" intersex children moved her to become a patient rights' activist. By bringing evidence to physicians and the public, she helped change the medical system. But even as she worked to correct these injustices, Dreger began to witness how some fellow liberal activists, motivated by identity politics, were employing lies and personal attacks to silence scientists whose data revealed inconvenient truths. Troubled, she traveled around the country digging up sources and interviewing the targets of these politically motivated campaigns. Among the subjects she covers in the book are the anthropologist Napoleon Chagnon, falsely accused in a bestselling book of committing genocide against a South American tribe; the psychologist Michael Bailey, accused of abusing transgender women; and the evolutionary biologist E. O. Wilson, accused of fomenting rightwing ideas about human nature. Galileo's Middle Finger describes Dreger's long and harrowing journey back and forth between the two camps for which she felt equal empathy: social justice warriors and researchers determined to put truth before politics"--